Simple damage model for cracked thin plate tensile test - Muhammad Izzat Shazali, Mohd Ramli (2012)
Simple damage model was a preliminary study in order to identify the need of assessment of method for cracked thin plate because the important for safe operation and maintenance especially in oil and gas industry. This study was dividing into 2 step which is experimental and FEA analysis using MSC PATRAN Software. For this project, the Finite Element Analysis result will compare to the experiment and the parameter will be added to see the change in the coalescence load versus crack size diagram between experiment and simulation. For the experiment, the project scope was focus on the API Grade B Specimen that has been machining into ASTM E8 standard size of tensile test specimen. Crack size for the specimen has been varying into 3 different sizes which are 4mm, 6mm, and 8mm crack size in order to examine the maximum tensile stress, strain and load for different crack size of the specimen. Afterward, using MSC Marc Patran Simulation the parameter will be added to generate simple damage model equation accurately and the results of finite element analysis can simplify working process and reduce working time to do an experiment. In the analysis, the parameters used are 2mm, 4mm, 6mm and 8mm crack size and also included in the analysis the material yield strength and poisson ratio. Based on the experimental and analysis, stress versus strain graph obtained and the result of the maximum stress, strain and load for the uncrack specimen and other parameter are compared. Besides that, simple damage model equation was obtained from load versus crack size diagram in order to predict the maximum load from various size of crack by using crack as the x parameter and y as the value of maximum load from finite element analysis result. These finding led to the conclusion that the maximum load are proportional to the crack size which is bigger the crack size of the specimen, the maximum load are decreased